Prostate Volume Changes during Extreme and Moderately Hypofractionated Magnetic Resonance Image-guided Radiotherapy. Issue 9 (September 2022) - Alexander, S.E.; McNair, H.A.; Oelfke, U.; Huddart, R.; Murray, J.; Pathmanathan, A.; Patel, P.; Sritharan, K.; van As, N.; Tree, A.C.
Abstract: Aims: Prostate morphological changes during external beam radiotherapy are poorly understood. Excellent soft-tissue visualisation offered by magnetic resonance image-guided radiotherapy (MRIgRT) provides an opportunity to better understand such changes. The aim of this study was to quantify prostate volume and dimension changes occurring during extreme and moderately hypofractionated schedules. Materials and methods: Forty prostate cancer patients treated on the Unity 1.5 Tesla magnetic resonance linear accelerator (MRL) were retrospectively reviewed. The cohort comprised patients treated with 36.25 Gy in five fractions ( n = 20) and 60 Gy in 20 fractions ( n = 20). The volume of the delineated prostates on reference planning computed tomography (fused with MRI) and daily T2-weighted 2-min session images acquired on Unity were charted. Forty planning computed tomography and 500 MRL prostate volumes were evaluated. The mean absolute and relative change in prostate volume during radiotherapy was compared using a paired t -test ( P value <0.01 considered significant to control for multiple comparisons). The maximum dimension of the delineated prostate was measured in three isocentric planes. Results: Significant prostate volume changes, relative to MRL imaging fraction 1 (MRL#1), were seen at all time points for the five-fraction group. The peak mean relative volume increase was 21% ( P < 0.001), occurring at MRL#3 and MRL#4 after 14.5 and 21.75 Gy, respectively. Prostate expansion was greatest in the superior–inferior direction; the peak mean maximal extension was 5.9 mm. The maximal extension in the left–right and anterior–posterior directions measured 1.1 and 2.2 mm, respectively. For the 20-fraction group, prostate volume increased relative to MRL#1, for all treatment time points. The mean relative volume increase was 11% ( P < 0.001) at MRL#5 after 12 Gy, it then fluctuated between 8 and 13%. From MRL#5 to MRL#20, the volume increase was significant ( P < 0.01) for 12 of 16 time points calculated. The peak mean maximal extension in the superior–inferior direction was 3.1 mm. The maximal extension in the left–right and anterior–posterior directions measured 1.7 and 3.7 mm, respectively. Conclusion: Significant prostate volume and dimension changes occur during extreme and moderately hypofractionated radiotherapy. The extent of change was greater during extreme hypofractionation. MRIgRT offers the opportunity to reveal, quantify and correct for this deformation. Highlights: Prostate volume significantly increases during extreme and moderately hypofractionated EBRT. Prostate dimension changes during EBRT are greatest in the superior-inferior direction. MRIgRT offers opportunity to reveal, quantify and correct for prostate volume changes during hypofractionated EBRT.